Reclassification of Candida guilliermondii FTI 20037 as Candida tropicalis based on molecular phylogenetic analysis - Lima,Luanne Helena Augusto (2003)
Yeasts of the genus Candida are of clinical importance and also have many industrial applications, mainly in the food industry. The yeast Candida guilliermondii FTI 20037 has been extensively studied in order to establish a biotechnological process for the production of xylitol. The goal of this study was to verify the taxonomic classification of this strain based on the analysis of rDNA sequences and the xyl1 gene. DNA fragments from these sequences were amplified by PCR and BLAST analysis revealed strong identity with the corresponding sequences from Candida tropicalis. Based on these results, we propose that C. guilliermondii FTI 20037 must be reclassified as C. tropicalis.